Credit Default Swaps: Are they Useful or Lethal for Financial Stability - Anees, Fuzail (2006)
The dissertation is aimed at studying the impact of the recently developed credit transfer instruments namely credit derivatives. In recent years the credit derivative market has witnessed a rapid growth and they are used by financial institutions such as Investment banks as a risk management tool to manage risk in order to reduce or transfer the risk. This dissertation will also look at the high concentration of credit derivatives within the credit derivative market and how such high concentration can have an impact on the financial stability. Although there is a high concentration within the market for credit derivatives, the main threat to the financial stability lies within the sellers market.